Factors Influencing the Use of Dhami Service among its Users at Kathmandu, Nepal - Sharma, Ira; Uprety, Deepak (Naresuan University Journal: Science and Technology (NUJST); Vol 26 No 2 (2018): April-June 2018, 2018)
Dhami service is a form of shamanic healing for the problems which they thought to be due to spiritual or super natural beings. In Nepal, majority of the people practice traditional medicine for health care. Globally, the use of alternative medicines, which still do not have scientific proof of being safe, is much common. Moreover, why people still have faith on them is not much clear yet. This study aims to identify the factors associated with use of dhami service in Kathmandu, Nepal. It is a descriptive, cross-sectional study carried out in Kathmandu Nepal in 2015. The primary information were collected with the help of structured questionnaires from the patients going to a dhami centre in 15 days period between 7 to 11 am. The study adopted census method and face to face interview of the patients was taken with the help of pretested questionnaire. The descriptive analysis was shown in frequency tables and charts. The Chi-square Statistics was used for bivariate analysis.      More than half of the respondents often used dhami services. Four fifth of the users were  female. More than half of them were illiterate and belonged to age group 26-35. Majority (38.54%) of the users were from Tamang community with highest being Buddhists (58.33%), followed by Hindus (40.63%).  The use of dhami service was statistically associated (p-value<0.05) with age, education, religion and the type of disease, whereas, no such associations (p-value>0.05) were found with gender, ethnicity, perceived satisfaction, family income, communicable/ non communicable disease and accessibility to modern health services. Therefore, public awareness and health education is necessary to convince them for wider and safer use of scientific health care services. K eywords: Dhami, Traditional medicine, Shamanic medicine, Nepal
Keywords: Dhami, Traditional Medicine, Faith Healer